2015
DOI: 10.31648/oej.3150
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Economy, ICT and Economic Growth in the CEE Countries

Abstract: This paper focuses on the relationship between Information and Communication Technologies, GDP growth and productivity in the Central and Eastern European (CEE) countries. It elaborates on measures of the digital economy/information society, emphasizing the role of complementary factors to ICT that are crucial for the productive use of these General Purpose Technologies. The paper discusses the impact of technical progress, induced by the development of ICT, on sources of economic growth by describing changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Other parts of the literature (Negroponte, 1998;Steinmueller, 2001;Arendt, 2015) tend to support the idea that low-income countries can converge with high-income countries through the digitalization of their governments. The impact of ICT on economic growth in developing countries could be triggered by increased productivity (Steinmueller, 2001), reduced transaction costs and accelerated the process of knowledge creation.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Other parts of the literature (Negroponte, 1998;Steinmueller, 2001;Arendt, 2015) tend to support the idea that low-income countries can converge with high-income countries through the digitalization of their governments. The impact of ICT on economic growth in developing countries could be triggered by increased productivity (Steinmueller, 2001), reduced transaction costs and accelerated the process of knowledge creation.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The related literature on the relationship between e-government and economic growth shows that the digital government is likely to increase the economic growth (Aker and Mbiti, 2010;Acemoglu and Robinson, 2013;World Bank, 2015;Myovella et al, 2019). Despite the more important role that egovernment can play for economic growth, its effect may depend on the level of development of a country (Dewan and Kraemer, 2000;Steinmueller, 2001;Arendt, 2015;Srivastava and Panigrahi, 2016). The study of Dewan and Kraemer (2000) finds that ICT is associated with increased economic growth in developed countries, whereas it is insignificant for developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chavula (2013) also showed that mobile and landline telephones significantly improved living standards in Africa. However, some studies (Negroponte, 1998;Steinmueller, 2001;Arendt, 2015) have opposed the notion that LICs are 'leapfrogging' in growth compared to HICs due to the use of ICT. They provide an example of this observable fact in Africa, indicating a high rate of mobile communication usage as a proxy for ICT.…”
Section: Impact Of Ict (Positive Negative and Insignificant)mentioning
confidence: 99%
“…The digital economy has demonstrated a strong resilience through a steady growth achieved against the trend [ 6 ]. It represents the future trend to transform traditional manufacturing into digital and intelligent manufacturing, showing the characteristics of digitization such as the reform of production methods driven by big data and complex manufacturing systems, the networked circulation of production elements, and the construction of the entire value chain [ 7 ]. Undeniably, the digital economy provides new options for the green transformation and upgrading of manufacturing through the in-depth integration of digital technology and physical enterprises, the innovation breakthroughs of new digital technologies such as big data, artificial intelligence, and the Internet of Things, as well as the effective interaction between manufacturing and service industries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%